2022
DOI: 10.18178/ijiet.2022.12.1.1586
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and Flipped Learning: Which Enhances Students’ Academic Performance Better?

Abstract: Most of the learning institutions even before the global pandemic are using a blended learning strategy. One of the most promising and leading blended-strategy today is the Flipped Classroom Model (FCM). FCM, often called as inverted classroom or reversed instruction, is a teaching model where the content of the study is given outside the classroom and homework is done inside the classroom. Previous researches yields different results when FCM is compared with traditional learning in enhancing students’ academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Past studies have found that flipped learning has many benefits for students, including increased performance [1,8,32,50], increased engagement and motivation [6,48], increased self-regulation [58], increased student autonomy [2,39], increased student collaboration [63], increased creativity [25], higher course satisfaction [27], and increased effectiveness of soft skills [8]. Flipped learning can achieve the same student outcomes as traditional courses with less "seat time" (p. 227), meaning that there are opportunities for flipped classrooms to enhance the efficiency of higher education learning by reducing the amount of staff-student contact necessary [4].…”
Section: Flipped Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies have found that flipped learning has many benefits for students, including increased performance [1,8,32,50], increased engagement and motivation [6,48], increased self-regulation [58], increased student autonomy [2,39], increased student collaboration [63], increased creativity [25], higher course satisfaction [27], and increased effectiveness of soft skills [8]. Flipped learning can achieve the same student outcomes as traditional courses with less "seat time" (p. 227), meaning that there are opportunities for flipped classrooms to enhance the efficiency of higher education learning by reducing the amount of staff-student contact necessary [4].…”
Section: Flipped Learningmentioning
confidence: 99%
“…In order to shed clarity on the uncertainty surrounding the effectiveness of flipped learning, Shi et al [55] and Sablan and Prudente [50] carried out more recent meta-analyses. Sablan and Prudente [50] found a strong effect size for flipped learning increasing academic performance of mathematics students across several phases.…”
Section: Flipped Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…ProScholar Insights (PSI) Volume 2, Issue 1 (2023) | DOI: 10.62997/psi.2023a.54109 Sablan and Prudente (2022) stated that the Flipped Classroom Model is a valuable approach for enhancing academic performance in subjects like Physics and Mathematics, regardless of class size or geographical location.…”
Section: Effectiveness Of Flipped Classrooms In Promoting Student Lea...mentioning
confidence: 99%
“…Blended learning shows higher performance compared to conventional understanding [12]. Blended learning can make learning implementation more effective and student outcomes better [13], and the blended learning Flipped Classroom Model can improve student academic achievement better than traditional learning [14].…”
Section: Introductionmentioning
confidence: 99%